A gestão dos recursos e competências e a formação da vantagem competitiva - um estudo sobre pequenas empresas beneficiadas por programa governamental de apoio - Kenski, Victor Wolowski (2011)
Small technology-based startup companies need to obtain a set of resources to establish themselves in the market and obtain a competitive advantage. They usually draw on external sources of support and financing to obtain these resources. This research is about startups which drew on the Innovative Program for the Small Enterprise (PIPE), granted and managed by the São Paulo Research Foundation (FAPESP). The goal is to analyze the way they developed a competitive advantage, the strategies they adopted and the importance of PIPE in this process. The research investigates the starting conditions, the evolution with the new resources and the situation that ensued from the creation of the competitive advantage. Ten companies were studied through a simple qualitative research based on interviews with their managers. The results show that the performances varies with the resources obtained by partners in the company s early days and with the capabilities to search the remaining resources and harmonically integrate them to the existing ones. They also show the positive influence of PIPE in obtaining the required resources and generating competitive advantages.